Kerjasama politik Melayu-Islam: Analisis hubungan UMNO-PAS dari tahun 1968 hingga 1978 / Mohammad Tawfik Yaakub - Mohammad Tawfik , Yaakub (2018)
This study discusses Malay-Muslim Political Cooperation: An Analysis on UMNO-PAS Relationship from 1968 until 1978. It aims to identify events that affect Malay-Muslim political cooperation in 1973, assessing the political dynamism of UMNO-PAS between 1968 to 1978, and to analyze the impact of political cooperation UMNO-PAS to the development of the Malay-Muslims. To proceed with this research, the theory of cooperation and concept of Tahaluf Siyasi are being selected as the analytical tools, as these approaches are related to the study of Malay-Muslim political cooperation. This collects data from primary and secondary sources. The primary source was obtained through interviews with former leaders and the leaderships of both political parties, while the secondary sources comprise books, theses, and journals published related to the research. These data are then analysed qualitatively. Based on the analysis the study found that there were certain events that affect the Malay-Muslim political cooperation in 1973, the existence of political dynamism between UMNO-PAS and its impact to the political cooperation development of the Malay-Islamic politics in this country. This research poses important insights that could contribute to the process of Malay- Muslim political cooperation particularly involving UMNO and PAS.